A Comparison of Different Murine Models for Cytomegalovirus‐Induced Sensorineural Hearing Loss. (24th April 2013) - Wang, Yong; Patel, Rusha; Ren, Chongyu; Taggart, Michael G.; Firpo, Matthew A.; Schleiss, Mark R.; Park, Albert H.
Abstract : Objectives/Hypothesis: To compare three different inoculation techniques for the development of cytomegalovirus (CMV)‐induced sensorineural hearing loss (SNHL) in a mouse model. Study Design: A prospective experimental animal study. Methods: BALB/c mice underwent inoculation using green fluorescent protein‐expressing mouse cytomegalovirus (mCMV‐GFP) via transtympanic (TT), intraperitoneal (IP), or intracranial (IC) routes. Control mice received an equal volume of saline. Hearing thresholds were measured using both distortion product otoacoustic emissions (DPOAE) and evoked auditory brainstem response studies (ABR). Cochleas were harvested for histological examination and cytocochleogram. Results: No mice in the TT or IP groups showed significant hearing loss. All infected mice in the IC group showed significantly elevated ABR and DPOAE thresholds at 4 weeks of age. Ten mice (55%) had profound hearing loss (≥80 dB) at 4 weeks of age, while the other eight mice (45%) initially showed moderate hearing loss (≤20 dB), which progressed to profound hearing loss by 6 to 8 weeks. Asymmetric hearing loss was seen in 40% of the mice. Temporal bone histology showed diffuse loss of outer hair cells (OHC). Green fluorescent protein (GFP)‐labeled virus was abundant in the spiral ganglion and adjacent to the scala tympani at the basal region of the cochlea at 7 days postinjection, and devoid of GFP labeling by 14 days postinfection. Conclusions: Intracerebral injection of mCMV preferentially causes mCMV‐mediated hearing loss relative to IP or TT injections. These results are consistent with the hearing loss reported in human congenital infection and may have implications for understanding the pathophysiology of CMV‐mediated labyrinthitis. Level of Evidence: N/A. Laryngoscope, 123:2801–2806, 2013